GFOGER Peptide Modifies the Protein Content of Extracellular Vesicles and Inhibits Vascular Calcification - Mansour, Ali; Darwiche, Walaa; Yaker, Linda; Da Nascimento, Sophie; Gomila, Cathy; Rossi, Claire; Jung, Vincent; Sonnet, Pascal; Kamel, Saïd; Guerrera, Ida Chiara; Boullier, Agnès; Ausseil, Jérôme (Frontiers in Cell and Developmental Biology, 2020)
Objective- Vascular calcification (VC) is an active process during which vascular smooth muscle cells (VSMCs) undergo an osteogenic switch and release extracellular vesicles (EVs). In turn, the EVs serve as calcification foci via interaction with type I collagen (COL1). We recently showed that a specific, six-amino-acid repeat (GFOGER) in the sequence of COL1 was involved in the latter’s interaction with integrins expressed on EVs. Our main objective was to test the GFOGER ability to inhibit VC. Approach- We synthesized the GFOGER peptide and tested its ability to inhibit the inorganic phosphate (Pi)-induced calcification of VSMCs and aortic rings. Using mass spectrometry, we studied GFOGER’s effect on the protein composition of EVs released from Pi-treated VSMCs. Results- Calcification of mouse VSMCs (MOVAS-1 cells), primary human VSMCs and rat aortic rings was lower in the presence of GFOGER than with Pi alone (with relative decreases of 66%, 58% and 91%, respectively; p<0.001 for all). No effect was observed with the scramble peptide GOERFG. A comparative proteomic analysis of EVs released from MOVAS-1 cells in the presence or absence of Pi highlighted significant differences in EV protein content. Interestingly, the expression of some of the EV proteins involved in the calcification process (such as osteogenic markers, TANK-binding kinase 1 and casein kinase II) was diminished in the presence of GFOGER peptide (data are available via ProteomeXchange with identifier PXD018169*). The decrease of osteogenic marker expression observed in the presence of GFOGER was confirmed by q-RT-PCR analysis. Conclusion- GFOGER peptide reduces vascular calcification by modifying the protein content of the subsequently released EVs, in particular by decreasing osteogenic switching in VSMCs.